Rituximab treatment for chronic steroid-dependent Henoch-Schonlein purpura: 8 cases and a review of the literature - Courtney B. Crayne; Esraa Eloseily; Melissa L. Mannion; Saji P. Azerf; Peter Weiser; Timothy Beukelman; Matthew L. Stoll; Daniel I. Feig; T. Prescott Atkinson; Randy Quentin Cron (BMC, 2018)
Abstract Background Henoch-Schonlein purpura (HSP) is a small vessel vasculitis that is characterized by non-thrombocytopenic purpura, abdominal pain, arthritis, and glomerulonephritis. Typically, HSP is self-limited requiring only supportive care, but more severe cases may require corticosteroid (CS) treatment. Rarely, a subset of these patients has persistent rash, arthritis, abdominal involvement, or renal disease despite treatment with CS, or has disease recurrence on CS tapering. Refractory HSP has been effectively treated with a variety of CS sparing therapies. For life-threatening refractory HSP, the B cell depleting agent, rituximab (RTX), has been reported as beneficial for children with substantial renal or central nervous system involvement. However, RTX use for children with less severe HSP, but chronic CS dependent disease refractory to CS sparing immunomodulatory agents, has been less well explored. Herein, we describe 8 children treated with RTX for chronic refractory HSP and report a reduction in recurrent hospitalizations and eventual CS discontinuation. Methods This is a retrospective analysis of eight children who were treated with RTX for chronic CS dependent HSP during the years 2006-2014 at a single institution. A chart review of the electronic medical record was performed to determine the presenting symptoms, the type and duration of treatment received, and the number of hospitalizations prior to and after RTX. The number of hospitalizations and oral corticosteroid burden were analyzed using the Wilcoxon signed rank test. Results Prior to receiving RTX, seven patients had at least one hospitalization for HSP (median 1.5, range 0-3). Following RTX, only two patients were hospitalized, each a single time for recurrent abdominal pain. The median oral CS burden was 0.345 mg/kg/day before RTX and 0 mg/kg/day at 6 months (p = 0.078), 1 year (p = 0.0625), and 2 years (p = 0.03) following RTX infusion. Seven out of eight children met remission criteria, defined as no active rash, arthritis, nephritis (hematuria and proteinuria), or gastrointestinal distress following RTX. No serious adverse events were noted. Conclusion Overall, RTX effectively reduced the number of hospital admissions and oral CS burden. RTX also helped most all children achieve clinical remission. RTX appears to be an effective and safe alternative for chronic CS dependent and immunomodulatory refractory childhood HSP.